Multiple fecal indices for predicting nutritional status of steers - Leite, Eneas Reis; Stuth, Jerry Wayne (Pesquisa Agropecuaria Brasileira, 2014)
This paper is part of a research to determine the relationship of dietary nutrition of free-roaming steers and associative fecal variables. Dietary parameter data were determined from previous studies. Fecal samples were analyzed for total nitrogen, soluble nitrogen, insoluble nitrogen, condensed tannins, proportions of fecal monocot and dicot fragments, and fecal organic matter. In general no fecal parameter by itself had a correlation with the dependent variables. A combination of fecal indexes accounted for more variation in dietary parameters than fecal nitrogen. Fecal nitrogen fractions did not improve the predictive power of multiple variable models. Equations predicting dietary crude protein yielded the highest coefficients of correlation.